The quality of friendship and its relationship to moral and social intelligences among students of Tafila Technical University - Al-Ghababsheh, Rana Ahmed; Thawabieh, Ahmad Mahmoud (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the degree of friendship quality, moral intelligence, and social intelligence, and the relationship between among Tafila University students’, in addition to identifying the effect of the variables (sex, college, and program) and their differences of the study on the degree of friendship quality, the study adopted the descriptive correlative approach for its relevance to the nature of the study, and its variables. The study- sample was consisted of (770) male and female students (10% of the study population), they were chosen by the stratified random method. To achieve the objectives of the study 3 scales was developed: friendship quality scale, moral intelligence scale, and social intelligence scale, its psychometric characteristics was confirmed. The results of the study showed that university students have high degrees of friendship quality, moral and social intelligences, the results showed positive statistically significant correlation between friendship quality, moral intelligence, and social intelligence, finally, the results indicated that the differences in the degree of friendship quality that attributed to the variables (sex, college, and academic program) was not significant. The study recommended the necessity of expanding the study of the concept of friendship quality, in terms of its stages of growth and development, and linking it with different variables, in addition to its positive impact on individuals, activating group activities, and promoting cooperative work at the university to allow positive interaction among students, which helps to maintain To form positive friendship relationships, and to include courses on the concept of friendship and its components and characteristics within university courses to enhance its positive role in raising the level of mental health of individuals.